An Analysis of Students Low Motivation in Learning English at Tenth Grade of SMA Al Irsyad - Rosnaningsih, Asih; Mustainah, Ina Anifatul; Firda, Alindia; Ruhimah, Ruhimah; Azhari, Mutiara Meiza (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
This study aims to analyze the low motivation of students in learning English in tenth grade at SMA Al Irsyad Banten. The research adopted a qualitative approach using several data collecting techniques namely interviews, direct observations, and analysis of relevant documents. The subject of this study was a tenth grade class with twenty students and conducted interviews with three students and one teacher.The findings reveal that the cause of low motivation of student are divided into internal and external factors. Between the two factors, the most dominant factors is internal. That internal factors such as, lack of interest, difficulty in understanding English, and boredom are the primary causes of low motivation amomg student. Additionally, external factors including insufficient family support, limited interaction with teachers, in effective teaching methods, and inadequate learning facilities, also contribute signifacantly. Challenges in mastering grammar, limited vocabulary, and poor comprehension of materials further underminds student confidence and interest of learning. The study highlights the need for stronger family support, the adoption of more communicative and varied teaching methods, and improved learning facilities to enhance student motivation in learning English.